Challenges in innovation and investment in small business and private entrepreneurship - Ro’ziyeva Dilobar Isomjonovna (International Journal on Economics, Finance and Sustainable Development, 2021)
The given article discusses the role of innovation-investment in the development of small business and private entrepreneurship, ways to increase the innovative potential of entrepreneurship, as well as the role of venture entrepreneurship in supporting small businesses and entrepreneurship, as a source of commercialization of high-tech research.